2020
DOI: 10.1021/acschembio.0c00114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Crystal Structure of the Human DHTKD1-Thiamin Diphosphate Complex

Abstract: DHTKD1 is the E1 component of the 2-oxoadipic acid dehydrogenase complex (OADHc), which functions in the L-lysine degradation pathway. Mutations in DHTKD1 have been associated with 2-aminoadipic and 2-oxoadipic aciduria, Charcot-Marie-Tooth disease type 2Q (CMT2Q) and eosinophilic esophagitis (EoE). A crystal structure and inhibitors of DHTKD1 could improve the understanding of these clinically distinct disorders, but are currently not available. Here we report the identification of adipoylphosphonic acid and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…There are, however, X-ray structures available for the N-terminally truncated E. coli E1o Δ77 (39% identity, missing the N-terminal 77 amino acids) [ 66 ], the N-terminally truncated Mycobacterium smegmatis α-ketoglutarate decarbo-xylase ( Ms KGD Δ115 , 41% identities, missing the N-terminal 115 amino acids) [ 67 ], the Ms KGD Δ360 catalytic domain, which showed overall structural similarity to the E. coli E1o [ 68 ], and the Ms KGD Δ360 catalytic domain in complex with phosphonate analogues of OG [ 69 ]. X-ray structures were recently reported for the N-terminally truncated human E1a (residues 45-919, missing the N-terminal 44 residues) at 1.9 Å [ 35 ] and for human E1a (residues 25-919, missing the N-terminal 24 residues) at 2.25 Å resolution (38.5% identities between E1o and E1a) [ 36 ]. Single-particle cryo-EM reconstruction of the E2o inner core domain at 4.7 Å global resolution [ 35 ] has been reported showing 24 E2o catalytic domains assembled as eight trimers and positioned at each of the eight vertices of the cubic core with octahedral symmetry ( Figure 2 B).…”
Section: The 2-oxoglutarate Dehydrogenase Complexmentioning
confidence: 99%
See 4 more Smart Citations
“…There are, however, X-ray structures available for the N-terminally truncated E. coli E1o Δ77 (39% identity, missing the N-terminal 77 amino acids) [ 66 ], the N-terminally truncated Mycobacterium smegmatis α-ketoglutarate decarbo-xylase ( Ms KGD Δ115 , 41% identities, missing the N-terminal 115 amino acids) [ 67 ], the Ms KGD Δ360 catalytic domain, which showed overall structural similarity to the E. coli E1o [ 68 ], and the Ms KGD Δ360 catalytic domain in complex with phosphonate analogues of OG [ 69 ]. X-ray structures were recently reported for the N-terminally truncated human E1a (residues 45-919, missing the N-terminal 44 residues) at 1.9 Å [ 35 ] and for human E1a (residues 25-919, missing the N-terminal 24 residues) at 2.25 Å resolution (38.5% identities between E1o and E1a) [ 36 ]. Single-particle cryo-EM reconstruction of the E2o inner core domain at 4.7 Å global resolution [ 35 ] has been reported showing 24 E2o catalytic domains assembled as eight trimers and positioned at each of the eight vertices of the cubic core with octahedral symmetry ( Figure 2 B).…”
Section: The 2-oxoglutarate Dehydrogenase Complexmentioning
confidence: 99%
“…Next, it was shown that the E1a has about 40-fold preference in catalytic efficiency with OA versus OG [ 43 ], suggesting that the E1a active center has evolved to accommodate the slightly longer OA compared to OG (one additional CH 2 group) substrate. These are important determinants for the rational design of E1a inhibitors that could be useful for diseases such as GA1 [ 36 ].…”
Section: Structural Insight Into the E1a Active Centermentioning
confidence: 99%
See 3 more Smart Citations